PENYUSUNAN KUMPULAN KATA BENDA SEBAGAI SUMBER TES MEMORI - Heru Prakosa; Esti Hayu Purnamaningsih; Sylvi Dewajani; Dicky Hastjarjo (Faculty of Psychology Universitas Gadjah Mada, 2008)
This paper describes the development processes of a stimulus pool for constructing memory test. The stimuli were noun words selected from Kamus Besar Bahasa Indonesia. Total noun words were 15,811 and only 3423 words were recognized by three tribes (Javanese, Sundanese and Balinese). Six hundred nouns were proportionally selected based on several features such as object category, word length, and initial alphabet. The 600 stimuli were assessed according to the level of concreteness, imagery and meaningfulness by 1100 subject form three different tribes. It was found there were some differences in the assessment as well some similarities in assessing noun words among the three tribes. The implication was discussed.